A multi-enzyme producing Bacillus subtilis YCXW-01: Isolation, genomic characterization, and potentials in tobacco stem degradation - Yang, Zongcan; Zhang, Quanbin; Fu, Bo; Zhang, Tingting; Feng, Yingjie; Zhao, Sensen; Wang, Huanhuan (Frontiers in Microbiology, 2025)
This study aimed to isolate a potent cellulase-producing bacterium from tobacco leaves to enhance the utilization value of tobacco stem waste.A strain designated YCXW-01 was isolated using sodium carboxymethyl cellulose as the sole carbon source. It was identified via morphology, physiology, and 16S rRNA sequencing. Growth kinetics, extracellular enzyme activities (cellulase, protease, amylase, xylanase), and whole-genome sequencing were performed. The practical efficacy of its crude enzymes was tested on tobacco stems.The isolate was identified as Bacillus subtilis. It exhibited a high cellulase activity of 10.97 U/mL, alongside substantial protease (23.11 U/mL), amylase (28.96 U/mL), and xylanase (23.68 U/mL) production. Genomic analysis revealed genes encoding key glycoside hydrolases (GH1, GH5, GH11, GH43). Treatment of tobacco stems with the crude enzyme extract reduced cellulose content by 35.3%. B. subtilis YCXW-01 demonstrates significant potential for tobacco waste biorefining due to its high, multi-enzyme activity and relevant genetic repertoire. The genomic data provide a foundation for elucidating its cellulolytic mechanism and guiding future applications.